Characterization of the phosphatidylinositol-glycan membrane anchor of human placental alkaline phosphatase. - Howard, A D (1987)
Placental alkaline phosphatase [orthophosphoric-monoester phosphohydrolase (alkaline optimum), EC 3.1.3.1] is a member of a diverse group of membrane proteins whose attachment to the lipid bilayer is mediated by a phosphatidylinositol-glycan. To investigate structural aspects of the glycolipid anchor, cultured WISH cells were used because we found that they produce the enzyme in abundant quantities. When cell suspensions were incubated with purified phosphatidylinositol-specific phospholipase C, most of the placental alkaline phosphatase was released from membranes in a hydrophilic form. On incubation of the cells with [14C]ethanolamine, [14C]myristic acid, or myo-[3H]inositol, each was incorporated into the phosphatase near the carboxyl terminus, showing that these components, which are found in other phosphatidylinositol membrane-linked proteins, are also present in placental alkaline phosphatase.